2013
DOI: 10.1186/1746-6148-9-10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and expression analysis of peptidase genes in the fish-pathogenic scuticociliate Miamiensis avidus

Abstract: BackgroundParasite peptidases have been actively studied as vaccine candidates or drug targets for prevention or treatment of parasitic diseases because of their important roles for survival and/or invasion in the host. Like other parasites, the facultative histophagous ciliate Miamiensis avidus would possess peptidases that are closely associated with the invasion into the host tissue and survival in the host.ResultsThe 17 genes encoding peptidases, including seven cathepsin-like cysteine peptidases, four ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…Ciliate proteases have been characterized as mainly cysteine proteases and have been described as virulence factors in numerous protozoan parasites (Sajid & McKerrow 2002;Param a et al 2004Param a et al , 2007aHerrmann et al 2006). Sequencing data for ciliate proteases are scarce (Seo et al 2013), even in databases such as MEROPS (Rawlings et al 2014); nevertheless, cysteine proteases appear to be the most abundant proteases in P. dicentrarchi (Param a et al , 2007a. In the present study, CUR affected the proteolytic activity of P. dicentrarchi proteases.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Ciliate proteases have been characterized as mainly cysteine proteases and have been described as virulence factors in numerous protozoan parasites (Sajid & McKerrow 2002;Param a et al 2004Param a et al , 2007aHerrmann et al 2006). Sequencing data for ciliate proteases are scarce (Seo et al 2013), even in databases such as MEROPS (Rawlings et al 2014); nevertheless, cysteine proteases appear to be the most abundant proteases in P. dicentrarchi (Param a et al , 2007a. In the present study, CUR affected the proteolytic activity of P. dicentrarchi proteases.…”
Section: Discussionmentioning
confidence: 51%
“…Leishmanolysin peptidase has also been investigated as a target in the development of antiparasitic treatments (Seo et al . ). Partial sequences of this protease have also been detected in ciliate parasites such as Ichthyophthirius multifiliis (Coyne et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The body region of the horse, the method of obtaining and the composition of PRP (considering the amount of platelets and leukocytes), the presentation form (liquid, gel), route and frequency of application, and the volume and time in which it is administered during the skin healing process are already mentioned as aspects related to the lack of sufficient evidence to confirm the effectiveness of PRP in the treatment of skin wounds. Using the ELISA immunoenzymatic technique, Giraldo et al [ 57 ] have recently reported a significant difference ( p < 0.001) in the PDGF-BB concentration in PRP gel (P-PRG; activated with 10% calcium gluconate) from Colombian Creole females and young horses (up to 5 years of age) compared with Argentine Creole males and horses over 10.1 years old. Textor et al [ 58 ], however, did not observe differences in the amount of growth factors TGF- β 1 and PDGF-BB in PRP of males and females.…”
Section: Resultsmentioning
confidence: 99%
“…Ciliates in the subclass Scuticociliatia Small, 1967 are commonly found in ecosystems worldwide and exhibit both a great biological and morphologic diversity (Foissner and Wilbert 1981;Fan et al 2011a,b;Foissner et al, 1994Foissner et al, , 2013Pan et al 2011;2013c;Seo et al 2013;Song and Wilbert 2002; Thompson and Kaneshiro, 1968;Whang et al 2013 About 20 genera and 40 species of scuticociliates have been reported in Chinese coastal waters (Fan et al, 2011a(Fan et al, , 2011bPan et al 2010Pan et al , 2011Pan et al , 2013cSong et al 2009). Because of their small size and the high degree of similarity in infraciliature, many scuticociliates are identified based upon a combination of characteristics observed in vivo and silver impregnation Pan et al 2010;Song and Wilbert 2000;Song et al 2001;Thompson 1964).…”
Section: Introductionmentioning
confidence: 96%